Peningkatan Keterampilan Bahasa Inggris Pemuda Karang Taruna Desa Mambalan Melalui Media Audio Visual - Zainudin Abdussamad; Sutarman Sutarman; Wahyu Kami Syarifaturrahman (LPPM Universitas Bumigora, 2021)
Mambalan is a village located in the Gunung Sari, West Lombok, where most of the population lived as farm laborers and stone breaking. A small income, of course, has an impact on the ability of parents to send their children to a higher level of education. Based on the conditions above, the writer and team are interested in conducting community service by providing English language training using audio-visual media for the youth organization. This training used an audio-visual media method with the aim of making the training activities more interesting and easier for the training participants. This English training activity has a positive impact on the youth organization of Mambalan village. These positive impacts are seen through the result of the training process. Within a few months of following the training process by using audio-visual media, the learning outcomes of the training participants increased. Before participating in the training, the training participants considered English was a difficult language to learn, but after participating in the training by using audio-visual media the trainees began to experience the convenience and the trainees thought that learning English using audio-visual media was fun.